Surgical management of non-cystic fibrosis bronchiectasis - Hiramatsu, Miyako; Shiraishi, Yuji (Journal of Thoracic Disease; Vol 10, Supplement 28 (October 19, 2018): Journal of Thoracic Disease (Medical and Surgical Management of Pulmonary Infections), 2018)
Non-cystic fibrosis bronchiectasis (bronchiectasis) is an abnormal dilatation of the bronchi and bronchioles, resulting from a prolonged recurrent infectious process due to various causes and predisposing factors. This disease has several etiologies and affects a heterogeneous population of patients. The most important viewpoint for the surgical management of bronchiectasis is to select appropriate candidates for surgery and conduct suitable anatomic lung resections at the right time under appropriate conditions. The ideal candidates for lung resection are symptomatic patients with focal disease due to truly localized bronchial pathology regardless of optimal and absolute medical management.